Efeitos genéticos e ambientais sobre a idade à primeira concepção de fêmeas suínas - Cavalcante Neto, A. [UNESP]; Lui, J. F. [UNESP]; Sarmento, J .L. R.; Ribeiro, M. N.; Monteiro, J. M. C. [UNESP]; Fonseca, C.; Tonhati, Humberto [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
The genetic and environmental factors that affect age at first conception (AFC) of gilts were evaluated, using 466 observations of Dalland animals (C-40). The software program MTDFREML was used to assess the genetic parameters on an animal model that included as fixed effect, contemporary group and, as random effects, the additive genetic, the common litter and the error. Mean value of AFC was 241.12±25.9 days, with CV of 8.5 %. Variance analysis showed that year (P<0.01), season (P<0.01) and herd effects (P<0.01) were important sources of variation of AFC. The throat effect (P=0.34) was not important for the AFC, but the mother of the gilts (P<0.01) was an important source of variation. The heritability estimate was 0.44±0.14 that this trait would yield genetic gain as a response to the selection.
Estimates of genetic and environmental effects on age at first conception of gilts
Keywords: Swine; non genetic effects; Genetic parameter; Puberty; Suíno; fatores não genéticos; Parâmetro genético; Puberdade